Performance Indicators KPIs in Employee Performance Evaluation - Ali , Oday Hussein (South Asian Journal of Social Sciences and Humanities, 2025)
A current application of several studies drawn from the body of existing research is the Key Performance Indicator (KPI), which this article adds to. Scholarly publications from journals, books, and various other references that serve as sources of literature are used to exemplify the qualitative technique used in this article in order to produce a result. The authors present the implementation details for their research outcomes and recommendations in this scientific work while highlighting how human resource science spans multiple industries via its reliance on scientific literature publications. Other researchers must be able to carry out the findings of this scientific paper in the future due to the performance management gap that has not been fully explored in relation to the current Key Performance Indicators.
Keywords: Performance Management; Key Performance Indicator; Employee Performance Evaluation